THE USE OF ACTIVE GAMES TO DEVELOP THE SKILLS OF MASTERING FOOTBALL ELEMENTS IN 10–12-YEAR-OLD STUDENTS (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the pedagogical significance of using active games in the process of effectively mastering and consolidating football elements among 10–12-year-old students. Taking into account the age-specific physical and psychological characteristics of middle school children, the advantages of the game-based method in teaching football technical elements (dribbling, passing, receiving, shooting, and defensive movements) are scientifically substantiated. In addition, examples of active games applicable in training sessions, their methodological organization, and expected outcomes are presented.
Keywords: Football, active games, technical skills, physical education, 10–12 years old, students, game method, agility, coordination.